Palliavite tratment of extrahepatic malign obstruction with plastic and metalic stents: a comparsion - M. Hadi YAŞA; C. YURDAYDIN; K. BAHAR; S. KARAYALÇIN; A.R. BEYLER; H. ÖZKAN; N. ÖRMECİ and A. DÖKMECİ (Turkish Journal of Gastroenterology, 2019)
-